Bis(N-isopropyl-N-methyldithiocarbamato-[kappa]2S,S')(1,10-phenanthroline-[kappa]2N,N')zinc - Abdul Wahab, Nor Asiken; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2011)
The ZnII atom in the title compound, [Zn(C5H10NS2)2(C12H8N2)], exists in a distorted cis-octahedral N2S4 donor set defined by two chelating dithiocarbamate anions as well as a 1,10-phenanthroline ligand. Each of the ligands coordinates in a symmetric mode. The crystal packing is stabilized by weak C-H...S, C-H...[pi](ZnS2C) and [pi]-[pi] [ring centroid distance between centrosymmetrically related pyridyl rings = 3.5955 (13) Å] interactions